Teachers’ Experiences and Perceptions in Using Interactive Whiteboards in EFL Classrooms - Hanna Sundari; Sinta Herawati; Suciati Suciati (Journal on Education, 2023)
Technological development is constantly advancing and keeps taking a bigger role in society, including in education. This development has taken interactive whiteboards to be used in the elementary classroom setting at present. The use of interactive whiteboards correctly can support the teaching-learning process in classrooms. This study was conducted to explore how teachers use the interactive whiteboard in the classrooms, what are the challenges encountered by teachers in teaching English using the interactive whiteboards, and what strategies teachers apply in overcoming those challenges. The study also investigated the teachers’ perception of interactive whiteboards. The research method used in this study is qualitative descriptive research involving four English teachers, students of grades one until six, also the principal of an elementary school. The data were obtained through observations, teachers’ questionnaires, a principal interview, and students’ survey. The technique for analyzing data was data condensation, data display, and conclusion drawing or verification. The study's results showed that teachers used interactive whiteboards to access educational software, such as the ones from the book publisher, Class Dojo, Edunav, and YouTube. Teachers also used interactive whiteboards as projectors to open the slides or presentations made by teachers, such as in PowerPoint, Ms.Word, and flipcharts. The main impacts of the lessons were increased use of the Internet, software, and visual resources as part of the lessons. There are some challenges during the implementation of interactive whiteboards in the classrooms, but teachers could apply some strategies to overcome them. The teachers and students perceived positively the use of interactive whiteboards in the classrooms. Teachers also had positive perceptions in terms of developing lessons using IWB, resources from the internet, and technical support. The negative responses were related to time, collaboration, and professional development.